Synthesis of Nanocomposition of Poly Acrylic Acid/Chitosan Coated-Magnetite Nanoparticles to Investigation of Interaction with BSA and IGG Proteins - Hamidreza Shagholani; Sayed Mehdi Ghoreishi (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2017)
Among the nanomaterial being applied for treatment and diagnosis field, magnetic NPs especially magnetite phase of iron oxide have been significantly interested due to their natural magnetic properties. In this study, a nanocomposition of poly (acrylic acid) and chitosan with Fe3O4 NPs were prepared in order to investigation for drug delivery systems and plasma protein adsorption. Synthesized NPs were studied by various technics including XRD, TEM, SEM, FT-IR, VSM, DLS, zeta potential and AAS. These NPs have superparamagnetic property that is essential for magnetic NPs to applying in body and drug delivery. Plasma protein adsorption is one of the most important issues for failure of nanocarriers function. In this work, BSA and IgG were used as models of proteins to study adsorption of protein onto NPs by UV-Vis spectroscopy method. Adsorption behavior of NPs for each protein was different. PAA-Fe3O4 NPs represent the lowest albumin adsorption and can be expected that have lower adsorption of protein in the body. The release profile of ascorbic acid from PAA-Fe3O4 NPs represents no sensitivity to pH, and NPs showed approximately same release behavior in pH 7.4 and 5.8.